Development of environmental performance and circular economy in the European Union countries: the case of “post-2004” members - Lacko, Roman; Hajduová, Zuzana; Dula, Radúz (Frontiers in Environmental Science, 2024)
The study aims to compare the environmental efficiency within the group of EU countries that joined the EU together in 2004 and to identify the common circular determinants of this efficiency. This study examines environmental efficiency among countries that joined the EU in 2004. Findings reveal that countries with a significant focus on services, particularly tourism, are more environmentally efficient.However, most countries are still heavily industry-oriented, with Bulgaria, Romania, and Croatia being the least efficient. The study also highlights the need for significant efforts to reduce greenhouse gas emissions. Interestingly, a positive correlation was found between resource productivity and the rate of use of circular materials, suggesting the importance of circular economy tools in improving the environment. Despite having a higher material and consumption footprint, these countries still produce a relatively high product and relatively low CO2 emissions. Based on these analyses, we found regional differences and the need for setting cluster policies within the circular economy at the EU level.